Complete Guide to Size Specification and Technical Design - Myers-McDevitt, Paula J. (New York : Bloomsburry, 2016)
"Complete Guide to Size Specification and Technical Design, 4th Edition, equips students with everything they need to know about measuring sample garments, creating fully graded spec sheets for grading patterns, fitting garments, and offering pattern alterations. Over 500 technical flats are clearly labeled with measurement points and instructions for taking measurements. The book includes spec sheets for different types of garments and industry forms within the context of the production process. Several sections are devoted to instruction on measuring the human body, PLM/PDM software, correct fitting issues (with suggestions for pattern alterations), and grade rules for both number and letter sizing. It also includes over 60 basic fashion flats and instructions on metric conversions in the Appendices"--
Includes index.
Keywords: Clothing and dress measurements -- Handbooks, manuals, etc; Tailoring -- Pattern design -- Handbooks, manuals, etc; DESIGN / Fashion; BUSINESS & ECONOMICS / Industries / Fashion & Textile Industry